Lack of evidence of acute ischemic tissue change in transient global amnesia on single-shot echo-planar diffusion-weighted MRI - Gass, Achim; Gaa, Jochen; Hirsch, Jochen; Schwartz, Andreas; Hennerici, Michael G. (Stroke, 1999)
Background and Purpose: There is uncertainty concerning the etiology of transient global amnesia (TGA). Previous CT and MRI studies have indicated that permanent structural abnormality is rare in TGA. Diffusion-weighted (DW) MRI is very sensitive to early ischemic parenchymal changes and has recently demonstrated embolic infarction in the posterior cerebral artery territory in 2 TGA patients. We report the findings of DW MRI in 8 patients in acute stages of TGA. - - Methods: Conventional and echo-planar DW MRI was performed in 2 patients in the active phase and 6 patients in the recovery phase (1 to 8 hours after cessation of anterograde memory dysfunction) of spontaneously occurring TGA. - - Results: None of the patients showed signs of hyperintensity on DW images or hypointensity on quantitative apparent diffusion coefficient (ADC) maps to suggest regional decreases of water mobility or acute T2 changes on transverse or coronal slices. - - Conclusions: We were unable to detect ADC or acute T2 changes with echo-planar DW MRI in patients with TGA, which suggests that mechanisms other than ischemic infarction may cause TGA. We did not identify spreading depression-associated changes of the ADC. Further refinement of MRI sequences may be necessary to detect subtle or transient signal change in brain parenchyma.